Rasionalitas Penggunaan Obat Benzodiazepine oleh Dokter Selama 10 Tahun Terakhir: Sebuah Literature Review - Anughrahani, Lilie; Wijaya, Diana; Ndraha, Suzanna; Rumawas, Marina Astrid (Universitas Kristen Krida Wacana, 2025)
Mental disorders have become a common problem globally. The World Health Organization shows that more than one in six people experienced mental health problems in 2016. Benzodiazepines, a drug that has been on the market since 1957, are often used to treat mental and behavior-related problems. Although effective for certain conditions, long-term use of benzodiazepines can cause significant side effects. Health regulations and guidelines suggest that treatment with benzodiazepines should be carried out rationally with reference to the Decree of the Minister of Health of the Republic of Indonesia in 2021 concerning the National Formulary. This literature aims to conduct a review to evaluate the rationality of the use of benzodiazepines by doctors in various countries over the past ten years. The method in this study is to search for articles through Google Scholar and Pubmed. The results obtained were that benzodiazepines are generally used to treat anxiety and sleep disorders. The maximum dose, which is according to the national formulary and the Food and Drug Administration, does not have a significant difference. Challenges that need to be addressed involve aspects of prescribing, such as ensuring the recipe is in accordance with the right indications, adhering to dosage restrictions, and paying attention to the maximum duration of use. Therefore, there needs to be clear rules to regulate this, supported by active socialization efforts to increase doctors' understanding and compliance with more rational prescribing practices.